The HeLa Pur factor binds single-stranded DNA at a specific element conserved in gene flanking regions and origins of DNA replication. - Bergemann, A D (1992)
A major site of DNA bending is located 1.6 kb upstream of the P1 transcription start site of the human c-myc gene, near the center of a reported zone of initiation of DNA replication. A repeated, purine-rich element, termed PUR, at the bend site is specifically bound by a protein in HeLa cell nuclear extracts. This protein has specific affinity for the purine-rich single strand of the element. Methylation interference maps a pattern of specific contact points with guanosine bases in a 24-mer oligonucleotide containing the element. UV cross-linking reveals that contact is made by a polypeptide of approximately 28 kDa. The PUR element is present at origins of replication and in gene flanking regions in a variety of eukaryotes from yeasts through humans. The consensus sequence GGNNGAGGGAGARRRR has been derived. This element is present near centers of regions of two mammalian loci (human c-myc and hamster dhfr) recently reported as initiation zones for DNA replication. A 24-mer oligonucleotide representing the hamster dhfr version of the PUR element effectively competes with the human c-myc version for binding to Pur.